Penerapan Knowledge Management System untuk Menciptakan Inovasi Studi Kasus UMKM Gerobak Becanda - Muhammad Arafah; Poltak Pancarian Situmorang (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to examine and examine the application of the Knowledge Management System to create innovation and change. The study was conducted on the Small and Medium Enterprises Angkringan Gerobak Becanda in Jakarta, to help generate trade competition and also achieve success with researchers helping to apply knowledge management that was previously uncreated or immature to create innovation and change.